Good Clinical Response in a Rare Aggressive Hematopoietic Neoplasm: Plasmacytoid Dendritic Cell Leukemia with No Cutaneous Lesions Responding to 4 Donor Lymphocyte Infusions Following Transplant - Amir Steinberg; Rina Kansal; Matthew Wong; Angela Lopez; Stephen Lim; Jean Lopategui; Michael Lill (Case Reports in Transplantation)
Blastic Plasmacytoid Dendritic Cell Neoplasm (BPDCN) is a rare and aggressive malignancy that usually presents with diffuse cutaneous lesions. While a favorable response to therapy occurs in a majority of cases, a sustained long-term response is uncommon. Most patients subsequently relapse within a year. In the following report, we present the case of a 41-year-old woman who has not displayed many of the clinical features traditionally associated with BPDCN. The patient received sporadic chemotherapy treatment over the course of 2 years, before undergoing an allogeneic stem cell transplant. Although she ultimately relapsed following her transplant, her disease has repeatedly returned into remission after donor lymphocyte infusion (DLI). Currently, the patient is in remission following her fourth DLI. We believe that allogeneic transplantation should be considered as front-line therapy for the treatment of this rare malignancy.